ASWAJA Education as an Alternative Healing Drug Addiction - Muhammad Afwan Romdloni; Yauwan Tobing Lukiyono; Muhammad Sukron Djazilan; Akhwani (Journal of Islamic Civilization, 2024)
The purpose of this article is to explore the potential interconnections between spirituality, health, and recovery through Islamic spiritual approaches that can help overcome inner urges in drug-dependent patients. An Islamic approach, particularly ASWAJA, can play a significant role in shaping a person's behavior and attitude, especially by promoting the attitudes and behaviors exemplified by the Prophet Muhammad and his role models. This can foster the development of positive character traits that the individual may not have previously possessed. This research employs a qualitative method with a phenomenological approach, featuring descriptive-analytical data presentation. To provide a comprehensive analysis, the study applies Islamic psycho-spiritual theory using an interpretive approach to explain and describe phenomena as expressed by participants. The consistent practice of ASWAJA by these drug-dependent individuals has demonstrated positive effects, particularly in their daily behavior, whether in social interactions within the community or in their worship of Allah SWT. Therefore, the ASWAJA approach shows potential as a method that can be further developed to address the challenges faced by dependent patients. Contextualizing the healing process with a spiritual approach offers an alternative treatment alongside medical interventions for drug-dependent individuals.